Guest‐Dependent Isomer Convergence of a Permanently Fluxional Coordination Cage. (14th January 2022) - Birvé, André P.; Patel, Harshal D.; Price, Jason R.; Bloch, Witold M.; Fallon, Thomas
Abstract: A fluxional bis‐monodentate ligand, based on the archetypal shape‐shifting molecule bullvalene, self‐assembles with M 2+ (M=Pd 2+ or Pt 2+ ) to produce a highly complex ensemble of permanently fluxional coordination cages. Metal‐mediated self‐assembly selects for an M2 L4 architecture while maintaining shape‐shifting ligand complexity. A second level of simplification is achieved with guest‐exchange; the binding of halides within the M2 L4 cage mixture results in a convergence to a cage species with all four ligands present as the "B isomer". Within this confine, the reaction graph of the bullvalene is greatly restricted, but gives rise to a mixture of 38 possible diastereoisomers in rapid exchange. X‐ray crystallography reveals a preference for an achiral form consisting of both ligand enantiomers. Through a combination of NMR spectroscopy and DFT calculations, we elucidate the restricted isomerisation pathway of the permanently fluxional M2 L4 assembly. Abstract : The first metallo‐supramolecular M2 L4 cages bearing shape‐shifting bullvalene ligands are prepared. The enormous potential complexity is limited by geometric constraints in solution, which converge to a single isomer in the solid state. Through detailed experimental and computational analysis, we map the fluxional nature of these systems.